1995
DOI: 10.1016/0014-5793(95)00891-c
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the 5′ untranslated region of the human α‐galactosidase A gene in high‐activity variants inhibits specific protein binding

Abstract: Recently, normal individuals were identified who had high levels of plasma ¢x-galactosidase A activity and a G to A transition in the 5' untranslated (5' UT) region of the ol-galactosidase A gene. Electrophoretic mobility shift assays revealed that the wild-type sequence at the site of this mutation complexed with specific nuclear proteins. A standard NF-KB site competed with the 5' UT site for formation of these DNA-protein complexes. Complex formation was inhibited by the transition mutation. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…One of the most common research applications of chimeric genetic reporter systems is in the analysis of cis-acting elements, like gene promoters; however, to the best of our knowledge, the functional consequences of the 5 0 UTR SNPs upon GLA gene expression have never been assayed in this manner. Overall, our results are consistent with the working hypothesis, based on observations in vivo that some of the minor 5 0 UTR SNPs alleles significantly affect aGal activity levels (Saifudeen et al 1995;Fitzmaurice et al 1997;Oliveira et al 2008a, b), and provide indirect evidence that the human GLA 5 0 UTR indeed contains sequences that are involved in the regulation of gene expression. These data also demonstrate, for the first time, that the 5 0 UTRdependent modulation of GLA gene expression may vary among different cell types.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…One of the most common research applications of chimeric genetic reporter systems is in the analysis of cis-acting elements, like gene promoters; however, to the best of our knowledge, the functional consequences of the 5 0 UTR SNPs upon GLA gene expression have never been assayed in this manner. Overall, our results are consistent with the working hypothesis, based on observations in vivo that some of the minor 5 0 UTR SNPs alleles significantly affect aGal activity levels (Saifudeen et al 1995;Fitzmaurice et al 1997;Oliveira et al 2008a, b), and provide indirect evidence that the human GLA 5 0 UTR indeed contains sequences that are involved in the regulation of gene expression. These data also demonstrate, for the first time, that the 5 0 UTRdependent modulation of GLA gene expression may vary among different cell types.…”
Section: Discussionsupporting
confidence: 91%
“…Because they were neither translated nor part of the mRNA Kozak consensus sequence for translation initiation, they were regarded as biologically neutral, but subsequent studies showed that the c.-30A allele was associated with increased aGal activity in plasma (Saifudeen et al 1995) and the c.-10T allele with decreased aGal activity in leukocytes (Oliveira et al 2008a, b), as compared to the corresponding WT alleles. Since the GLA 5 0 UTR c.-10 and c.-30 positions are within binding sites respectively for the MDBP and the NFkB and Ets families of TF, the effect of those two nucleotide transitions upon aGal expression in vivo might be mediated by modulation of transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations